Trans tales-2 - Shankaranarayana K; Girish, N (Ujire, 2020)
Trans Tales-2 is an anthology of translated stories focusing on the transgender community in India, compiled and edited by Shankaranarayana K and N. Girish. Published in 2020 by Manjushri Printers in Ujire, this collection compiles narratives from Kannada, Malayalam, and Hindi, aiming to highlight the experiences and identities of the third gender in India.
Keywords: Indian English Fiction; Indian English Literature